ANALISA UJI MINYAK UNTUK MENGETAHUI TEKANAN RESERVOIR, PERMEABILITAS, PARAMETER FRACTURING PADA SUMUR CBM LAPANGAN "X". - Harun Lubis, Alfino
Reservoir parameters such as pore pressure and permeability are vital to a successful coalbed methane (CBM) project. Measuring coal permeability is quite difficult, as it is highly stress dependent and core data may not represent in situ reservoir condition. Conventional well testing methods, for example pressure buildup/drawdown or injection/falloff have been used previously to determine in situ permeability of coal. However, these methods are costly and time consuming, especially for low permeability reservoir of CBM. Moreover, if fracture pressure is exceeded during an injection test, conventional analysis can give erroneous results. In the last decade, there has been a great deal of minifrac application as new well testing method in CBM reservoirs to overcome the disadvantages of conventional methods. Besides permeability and reservoir pressure, this test can also present the fracturing parameters needed for well stimulation. Experts already made numerous study about minifrac analysis. To many new practical engineers, the analysis may cause some difficulty because of various theories proposed. This paper presents the workflow of minifrac analysis and discusses the basic theory to determine permeability, pore pressure, and fracturing parameters. Only the most common methods in CBM industry are presented in the paper. In the end, a case study of a minifrac test from two different intervals in the same CBM well of X Field will be carried out.